Social Cohesion and Welfare States From Fragmentation to Social Peace - Lloyd, Christopher; Hannikainen, Matti (Taylor & Francis, 2022)
Aiming to go beyond reiterating the stereotypical narrative of the rise of welfare states, this interdisciplinary book examines the long-run historical processes of the development of the welfare state. It focuses on the complex political, social, economic and institutional transformations which give rise to these peaceful and cohesive societies. Welfare is crucial to the story of peaceful social integration and this book explores and explains this vital connection, taking a non-linear view of the history of moving from fragmentation to peace with comprehensive welfare institutions. Chapters collectively focus on three central areas: (a) types of socio-political fragmentation, (b) the interconnection of social, political, and economic forces that led to the institutionalisation of integrationist processes and policies (including re-distributional welfare systems), and (c) how this new institutional development helped achieve, or failed to achieve, social peace and welfare. The international panel of expert contributors provide case studies from a rich variety of country contexts, including Germany, South Africa, the Netherlands, Austria, and the Nordic Countries. This thought-provoking collection of essays is well suited for advanced students and researchers in social history, economic history, political economy and social policy.